Endoscopic endonasal repair of spontaneous sphenoid sinus lateral wall meningocele presenting with cerebrospinal fluid leak - Yıldırım, Ali Erdem (Medknow Publications & Media Pvt Ltd, 2014)
Spontaneous sphenoid sinus lateral wall meningoceles are rare lesions with an unknown etiology. Endoscopic endonasal technique is a considerable route in the treatment of this condition. The aim of this paper is to report the etiology, surgical technique, and outcome in a patient repaired via endoscopic endonasal approach. A 51-year-old male patient applied with rhinorrhea started three months ago after an upper respiratory infection. There were no history of trauma or sinus operation. Biochemical analysis of the fluid was positive for beta-2-transferrin. This asypthomatic patient had undergone for repairment of lateral sphenoid sinus meningocele with endoscopic endonasal transsphenoidal approach. After endoscopic endonasal meningocele closure procedure no complications occured and a quick recovery was observed. Endoscopic endonasal approach is an effective and safe treatment modality of spontaneous lateral sphenoid sinus meningoceles and efficient in anterior skull base reconstruction.